2016
DOI: 10.1016/j.ejvs.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography of Skin Changes in Legs with Chronic Venous Disease

Abstract: In legs with venous disorders, sonography refines clinical evaluation of the skin and may reveal changes not highlighted by inspection. Some of these changes could require further investigation because they have not yet been explained or described. Skin sonography should improve knowledge of the natural history of skin changes, as well as contribute to a better grading of venous diseases severity In particular, US evidence of cutaneous and subcutaneous changes in C2 legs should be considered to stratify the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 26 publications
1
25
0
Order By: Relevance
“…In edematous legs, the subcutaneous layer was found to be particularly thickened with a hypo-echoic pattern (Figure 2B). This finding is supported by a previous ultrasound study of the skin of C3 class leg edema that used the clinical etiology anatomy pathophysiology (CEAP) classification of venous disease, which also showed thickening of the subcutaneous layer [11].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In edematous legs, the subcutaneous layer was found to be particularly thickened with a hypo-echoic pattern (Figure 2B). This finding is supported by a previous ultrasound study of the skin of C3 class leg edema that used the clinical etiology anatomy pathophysiology (CEAP) classification of venous disease, which also showed thickening of the subcutaneous layer [11].…”
Section: Discussionsupporting
confidence: 71%
“…Previously published studies on the measurement of the thickness of the skin of the leg using ultrasonography have been reported in patients with chronic venous disease [11], lymphedema [12,13], synovitis with pitting edema syndrome (RS3PE) [14], and age-related diurnal changes of dermal edema [15]. Most of these previous studies have shown varied ultrasound patterns of subcutaneous edema.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultrasound technique as a characterization tool is not new. Its use has progressively increased in the field of dermatology over the past decade, providing information in the clinical examination of a wide range of diseases, with inflammatory skin diseases among them . In HS, ultrasound can map skin lesions, and its use helps identify the extent of the lesions more precisely than routine physical examination, as well as the inflammatory activity of these lesions with the use of colour Doppler.…”
Section: Discussionmentioning
confidence: 99%
“…There was broad disagreement on statement 3, indicating that the vast majority of specialists feel that C2 patients do not have the same clinical characteristics. In this regard, it should be kept in mind that CEAP classification is not a classification of severity, and the C2 subcategory comprises all types of varicose veins [40]. In fact, among C2 patients, there is a variety of risk factors and age, accounting for some variability [41].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ultrastructural morphology of venous valves in chronic venous disorders may not depend on age in patients with C2 disease [41]. It has also been demonstrated that there is a high degree of histological variability in patients with C2 disease with marked inflammation in some patients, which may help explain the different severity of symptoms among patients even with the same stage of disease [40,41]. Taken together, these considerations confirm that C2 is a subgroup that encompasses a wide variety of clinical characteristics and symptoms.…”
Section: Discussionmentioning
confidence: 99%